Marshall cavendish cambridge primary maths activity book 2 - Soh, Christina; Soon, Spario (Marshall Cavendish Education Singapore, 2017)
The "Maths 2, Activity Book" complements the Pupil's Book with a range of exercises designed to deepen understanding of more advanced topics. It features challenging problems, group activities, and creative tasks that encourage collaboration and reinforce learning in a playful manner.